2020
DOI: 10.1177/1362168820913985
|View full text |Cite
|
Sign up to set email alerts
|

The role of working memory in blocked and interleaved grammar practice: Proceduralization of L2 syntax

Abstract: Prior research showed that interleaved practice (studying multiple skills at once) is more effective than blocked practice (studying only one skill at a time). This study aims to replicate the benefits of interleaved practice on the proceduralization of second language (L2) syntax and further examines the role of working memory (WM) in different practice schedules. Sixty English learners studied five types of relative-clause constructions under either blocked- or interleaved-practice conditions. The blocked-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(40 citation statements)
references
References 63 publications
9
27
1
Order By: Relevance
“…However, four of the five ATI patterns were driven by the association between aptitude and breakdown fluency changes that were primarily observed in the blocked group. The unique role of aptitude in blocked practice is consistent with the findings yielded by previous research on L2 grammar learning (Suzuki et al, 2020). Nonetheless, it is worth noting that Suzuki et al (2020) examined grammar learning by distinguishing similar relative clause constructions pertaining to the oral picture description.…”
Section: Selective Roles Of Memory In Fluency Development Through Blocked Task Repetitionsupporting
confidence: 84%
See 3 more Smart Citations
“…However, four of the five ATI patterns were driven by the association between aptitude and breakdown fluency changes that were primarily observed in the blocked group. The unique role of aptitude in blocked practice is consistent with the findings yielded by previous research on L2 grammar learning (Suzuki et al, 2020). Nonetheless, it is worth noting that Suzuki et al (2020) examined grammar learning by distinguishing similar relative clause constructions pertaining to the oral picture description.…”
Section: Selective Roles Of Memory In Fluency Development Through Blocked Task Repetitionsupporting
confidence: 84%
“…Because the effects of interleaved practice on fluency development are not influenced by individuals' aptitudes at least examined in the study, interleaved practice may be suitable for L2 learners with lower aptitudes. In other words, interleaved practice may neutralize the levels of aptitudes (Suzuki et al, 2020). In contrast, learners with higher aptitudes (PSTM and associative memory) may take advantage of their strengths and benefit from engaging in blocked task repetition practice most.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accumulated evidence has suggested that the interleaving effect extends to L2 grammar learning (Nakata & Suzuki, 2019b; Pan, Tajran, Lovelett, Osuna, & Rickard, 2019; Suzuki & Sunada, 2019; Suzuki, Yokosawa, & Aline, 2020). The advantage of interleaved practice was found in the acquisition of the English tense–aspect–mood distinction (Nakata & Suzuki, 2019b) and Spanish past‐tense morphology (Pan, Lovelett, Phun, & Rickard, 2019), as well as in English subject/object relative clause constructions (Suzuki & Sunada, 2019; Suzuki et al., 2020). For instance, in Nakata and Suzuki's (2019b) study, EFL learners were introduced to five structures from the English tense–aspect–mood system: simple past, present perfect, first conditional, second conditional, and third conditional.…”
Section: Background Literaturementioning
confidence: 99%